The Effectiveness of Learning Materials Based on Local Potentials on Studentsâ€™ Interests and Learning Outcomes - Kholifahrini, Riska; Susilowati, Sri Mulyani Endang; Nugroho, Sunyoto Eko (LP3 Universitas Negeri Semarang, 2019)
This study aims to describe the effectiveness of learning materials based on local potentials on the improvement of studentsâ€™ interests and learning outcomes at SD N Malingmati II for Theme 1 â€œSave Living Things.â€ The research sample was students of grade 6 SD N Malingmati as many as 34 students. The type of research that is used in this study is quasi-experimental research with one group pre-test â€“ post-test design. Data were descriptively analyzed. The techniques of data collection used pre-test and post-test, as well as questionnaires. The result of the study showed that learning materials based on local potentials were effective in improving studentsâ€™ learning outcomes. Studentsâ€™ learning outcomes had N-gain 0.72 which was in the high category. The result of questionnaires about studentsâ€™ interest in science learning based on local potentials was in the excellent criteria. The highest interest percentage was in the aspect of concern for local potentials as much as 92%. The lowest interest percentage of the length of learning science was 85% because the students were not only focused on science only, but also integrated thematic learning.